Pengaruh Diameter Dan Panjang Serat Pelepah Sawit Terhadap Sifat Dan Morfologi Wood Plastic Composit (WPC) - Siti Sakinah; Bahruddin Bahruddin; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The length and diameter of the fibers of palm frond is one of the factors that affect the physical and mechanical properties of the material WPC. This study aims to determine the effect of fiber diameter and length of the palm fronds to the properties and morphology of wood plastic composite (WPC). WPC samples prepared by the method of melt blending the fibers of palm fronds, PP, Maleated polypropylene (MAPP), and paraffin for 65 minutes at a temperature of 170 ° C and a rotor speed of 80 rpm using the Internal Mixer. The length and diameter of the fibers of palm fronds used is ± 1 mm, 1 cm and 5 cm in diameter filler: - 40 ~ + 60 mesh, - 60 ~ + 80 mesh and - 80 ~ + 100 mesh. While the ratio of the weight ratio of PP / fiber palm fronds are 50/50 and 70/30. The test results showed that the best mechanical properties resulting in a length of 1 mm and the diameter of the fiber - 80 ~ + 100 mesh at a ratio of polypropylene / palm frond fibers 70/30 with a value of 16.44 MPa tensile strength and flexural strength 31.21 MPa. In testing the physical properties of the best value generated with the water content value of 8,61%, the absorption value of 1.78%, the highest density value of 0.99 g /cm3 and thickness swelling lowest value of 0.33%, while in the SEM testing, interaction between filler and matrix are still lacking thus forming agglomeration as a result of the fiber and the matrix material evenly mixed at WPC.Keywords: fiber diameter, fiber length, physical, mechanical, morphological, wood plastic composite